Comparative performance of Landim and Blackhead Persian sheep in Mozambique - Rocha, A.; McKinnon, D.; Wilson, R.T. (Elsevier, 1990)
Compares the performance of Landim and Blackhead Persian sheeLarger litter size of Landim sheep compared to Blackhead Persian and BHP X Landim, and similar parturition intervals in each genotype resulted in greater annual output of young in the Landim than in BHP or in BHP X Landim. Weights of all three genotypes were similar at birth, at 90 days, at 150 days and at 365 days. Breed did not affect the death rate at any of 10, 30, 90 or 150 days of age. Output of weaned lambs per breeding ewe per year was slightly higher in crossbred than in Landim or BHP but output per kg live weight of ewe did not differ among the genotypes. Year, season, type of birth, sex and ewe age significantly influenced most traits. Overall performance of Landim sheep was not different to that of the BHP indicating little if any advantage in using BHLandim sheep have large litter sizes in comparison to other African indigenous breeds and could themselvs be used to improve reproductive performance of other strains of sheep.